Systematic Literature Review: The Letter of the Ethnomathematics Approach in Improving Critical Thinking Skills - Faza Intan Azzahra; Nuriana Rachmani Dewi; Zaenuri Zaenuri; Walid Walid (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This study aims to examine the implementation of the ethnomathematics approach in mathematics learning to improve the critical thinking skills of junior high and high school students. The method used is a Systematic Literature Review (SLR) of 19 relevant articles published between 2020 and 2025. Articles were selected through Google Scholar, Semantic, and Scopus with strict inclusion and exclusion criteria. The analysis shows that the integration of local cultural contexts with mathematics material significantly improves critical thinking skills through the interpretation of mathematical concepts in real life. The summary of findings highlights an increase in motivation, conceptual understanding, and analytical skills, symbol interpretation, and mathematical argumentation. Many studies report successful implementation through various innovative learning models such as inquiry-based learning, problem-based learning, and the use of digital media such as 3D e-modules, Android applications, and virtual reality that link local culture with mathematics material. These findings recommend an ethnomathematics approach as a contextual strategy to improve student engagement, understanding, and critical thinking skills.